Biological and Immunological Characterization of a Functional L-HN Derivative of Botulinum Neurotoxin Serotype F - Zhiying Li; Bolin Li; Jiansheng Lu; Xuyang Liu; Xiao Tan; Rong Wang; Peng Du; Shuo Yu; Qing Xu; Xiaobin Pang; Yunzhou Yu; Zhixin Yang (Toxins, 2023)
Botulinum neurotoxins (BoNTs) can cause nerve paralysis syndrome in mammals and other vertebrates. BoNTs are the most toxic biotoxins known and are classified as Class A biological warfare agents. BoNTs are mainly divided into seven serotypes A-G and new neurotoxins BoNT/H and BoNT/X, which have similar functions. BoNT proteins are 150 kDa polypeptide consisting of two chains and three domains: the light chain (L, catalytic domain, 50 kDa) and the heavy chain (H, 100 kDa), which can be divided into an N-terminal membrane translocation domain (HN, 50 kDa) and a C-terminal receptor binding domain (Hc, 50 kDa). In current study, we explored the immunoprotective efficacy of each functional molecule of BoNT/F and the biological characteristics of the light chain-heavy N-terminal domain (FL-HN). The two structure forms of FL-HN (i.e., FL-HN-SC: single chain FL-HN and FL-HN-DC: di-chain FL-HN) were developed and identified. FL-HN-SC could cleave the vesicle associated membrane protein 2 (VAMP2) substrate protein in vitro as FL-HN-DC or FL. While only FL-HN-DC had neurotoxicity and could enter neuro-2a cells to cleave VAMP2. Our results showed that the FL-HN-SC had a better immune protection effect than the Hc of BoNT/F (FHc), which indicated that L-HN-SC, as an antigen, provided the strongest protective effects against BoNT/F among all the tested functional molecules. Further in-depth research on the different molecular forms of FL-HN suggested that there were some important antibody epitopes at the L-HN junction of BoNT/F. Thus, FL-HN-SC could be used as a subunit vaccine to replace the FHc subunit vaccine and/or toxoid vaccine, and to develop antibody immune molecules targeting L and HN domains rather than the FHc domain. FL-HN-DC could be used as a new functional molecule to evaluate and explore the structure and activity of toxin molecules. Further exploration of the biological activity and molecular mechanism of the functional FL-HN or BoNT/F is warranted.